A precise late Permian 40Ar/39Ar age for Central Iberian camptonitic lamprohyres - J.H. SCARROW; F. BEA; P. GONZÁLEZ MONTERO; J. F. MOLINA PALMA; ALAN VAUGHAN (Geologica Acta, 2006)
The Avila batholith of central Spain is composed, predominantly, of crustal-melt peraluminous granites cut by small-scale mafic alkaline bodies. Dating of the Gredos sector mafic camptonitic lamprophyre dykes was undertaken to constrain the Late Variscan tectonomagmatic evolution of the region. A well constrained late Permian, Capitanian, age of 264.5 ± 1.3 Ma was obtained by 40Ar/39Ar geochronology using amphibole separates. This new age clearly distinguishes the dykes from other episodes of alkaline mafic magmatism in the region. We suggest that the lamprophyre dykes were emplaced into already solidified granitoids after the tectonic control on magma generation changed from purely extensional to transtensional.